Pengendalian Persediaan Bahan Baku Vulkanisir Ban (Studi Kasus: PT. Gunung Pulo Sari) - Difana Meilani; Ryan Eka Saputra (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2013)
The problem of raw materials is the most fundamental issue for a manufacturing company, because the raw material is something that is very important for a production process. Companies must be able to maintain optimal raw material inventory that the production process can run smoothly so as to achieve the production target set by the company and can meet the demand of consumers. PT. Gunung Pulo Sari is one of the manufacturing company engaged in tire retreading. Here there are two types of main raw material of the tire retreading process is the rubber cold rare steak to cook and cook to cook hot rubber. PT. Gunung Sari Pulo do not meet the criteria of good inventory management. So far the company in order raw materials only based on estimates only. We conducted this study in order PT. Gunung Sari Pulo can manage them inventory system by finding the optimum safety stock, determine the total cost of the minimum size of the buyer to use the dynamic method, and the reorder point. Based on the research that has been done then the obtained value of safety stock is 18 units, the total minimum cost is Rp. Rp. 133 991 672, and reordering time (Reorder point) is 93 units.